Two-stage frequency regulation for wind turbines with adaptive coefficients and optimized power trajectory - Zhiting Zhou; Hui Li; Jie Zheng; Hongtao Tan; Xuewei Xiang; Ran Yao (International Journal of Electrical Power & Energy Systems)
Wind turbines support grid frequency by rotor decelerating and then accelerating, but the instant power imbalance caused by rotor speed recovery may lead to a secondary frequency drop. Existing frequency regulation strategies find it challenging to balance secondary frequency drop depth with rotor speed recovery time. To address this issue, a frequency regulation scheme for wind turbines with adaptive coefficients and optimized power trajectory is proposed, considering both the kinetic energy release stage and rotor speed recovery stage. This scheme aims to minimize power imbalance and rotor speed deviation without compromising primary frequency regulation performance. Initially, a two-stage system frequency response model is established to analyze factors affecting secondary frequency drop and rotor speed recovery time. Then, the fuzzy logic-based droop gain and segmented inertia gain are introduced as control strategies for the first stage. Additionally, the criterion for exiting frequency regulation and optimized power trajectory with smooth time-varying changes are implemented as control strategies for the second stage. Simulation results show that the proposed scheme adaptively improves the frequency nadir and effectively balances secondary frequency drop with rotor speed recovery time under various scenarios.